Chemically modified graphene sheets as potential sensors for organophosphate compounds(pesticide): A DFT study - Shivankar, Bhavana R.; Singh, Chandrodai Pratap; Krishnamurty, Sailaja (Applied Surface Science, 2023)
Owing to the extensive use of pesticides in agriculture and the threat posed to the environment and humankind, attention is drawn toward the need for its remediation from various sources, in particular from water. The adsorption characteristics of hydrophobic graphene and its BN doped counterparts are evaluated using DFT methodology, to assess their sensing potential towards notable pesticide molecules (Organophosphate pesticides (OPs) such as chlorpyriphos, parathion, methyl-parathion, and fenitrothion). To accomplish this, various elec-tronic properties such as band structure, DOS, Bader charge analysis, and CDD have been calculated. Interest-ingly, exothermic interactions (-0.1 eV to-2 eV) have been noted for all the OPs with NB doped single vacancy defect induced graphene surfaces. With an exception of FTN, all the other OPs showed significant changes in the electronic properties of surfaces as apparent from the change in band gap and nature of the band from indirect to direct. The appreciable adsorption energy, higher charge transfer, and notable variation in the band gap are the decisive factors behind the strong interaction exhibited by NB doped surfaces especially dg-(NB-2)2 (except FTN). These findings demonstrate the suitability of NB doped single vacancy defect induced graphene sheets for the detection of the studied OPs.
Keywords: Adsorption; BN doped graphene surfaces; Charge density difference; Density functional theory; Organophosphate pesticides

High-capacity V2N MXene for multivalent ion batteries: an Ab initio study - Saharan, Sunita; Ghanekar, Umesh; Shivankar, Bhavana R.; Meena, Shweta (Journal of Physical Chemistry C, 2024)
In this study, the electrochemical energy storage properties of V2N MXene as an electrode material for multivalent zinc (Zn2+) and calcium (Ca2+) ion rechargeable batteries have been studied using first-principles computations. Various properties like band structure, adsorption energy, diffusion kinetics, and open-circuit voltage are investigated using density functional theory. V2N MXene demonstrates metallic properties with a high structural stability and low diffusion barriers. Remarkably, Zn (976.4 mA h/g) and Ca (770.8 mA h/g)-adsorbed V2N MXene layers exhibit better storage capacity than the reported ones (517 mA h/g for zinc-intercalated CC@MnO2@Ti3C2TX and 598.63 mA h/g for calcium-intercalated V3C2/graphene). These findings make V2N MXene a highly promising cathode material for zinc and an anode material for calcium-ion batteries.

Investigation of cathinone analogs targeting human dopamine transporter using molecular modeling - Shivankar, Bhavana R.; Bhandare, Vishwambhar Vishnu; Joshi, Krati; Patil. Vishal S.; Dhotare, Priyanka Shrikant; Sonawane, Kailas Dasharath; Krishnamurty, Sailaja (Journal of Biomolecular Structure & Dynamics, 2024)
In a step towards understanding the structure–property relationship among Synthetic Cathinones (SCs), a combined methodology based on Density Functional Theory (DFT), Administration, Distribution, Metabolism, Excretion, and Toxicity (ADMET) predictions, docking and molecular dynamics simulations have been applied to correlate physicochemical descriptors of various SCs to their biological activity. The results from DFT and molecular docking studies correlate well with each other explaining the biological activity trends of the studied SCs. Quantum mechanical descriptors viz. polarizability, electron affinity, ionization potential, chemical hardness, electronegativity, molecular electrostatic potential, and ion interaction studies unravel the distinguishingly reactive nature of Group D (pyrrolidine substituted) and Group E (methylenedioxy and pyrrolidine substituted) compounds. According to ADMET analysis, Group D and Group E molecules have a higher probability of permeating through the blood–brain barrier. Molecular docking results indicate that Phe76, Ala77, Asp79, Val152, Tyr156, Phe320, and Phe326 constitute the binding pocket residues of hDAT in which the most active ligands MDPV, MDPBP, and MDPPP are bound. Finally, to validate the derived quantum chemical descriptors and docking results, Molecular Dynamics (MD) simulations are performed with homology-modelled hDAT (human dopamine transporter). The MD simulation results revealed that the majority of SCs remain stable within the hDAT protein’s active sites via non-bonded interactions after 100 ns long simulations. The findings from DFT, ADMET analysis, molecular docking, and molecular dynamics simulation studies complement each other suggesting that pyrrolidine-substituted SCs (Group D and E), specifically, MPBP and PVN are proven potent SCs along with MDPV, validating various experimental observations.

Polyvalent interaction and confinement to suppress polysulfide dissolution and improve electrocatalysis - Bharathkumar, H. J.; Shivankar, Bhavana R.; Krishnamurty, Sailaja; Chen, Dehong; Caruso, Rachel A.; Krishnamoorthy, Kothandam (CATALYSIS SCIENCE & TECHNOLOGY, 2024)
Keywords: cathode material; HIGH-CAPACITY; Particles; SULFUR CATHODE

Clove essential oil-supported disposable in-tip cellulose paper (DICP) device for facile extraction of anesthetic drugs from postmortem samples: a white analytical toxicology (WAT) approach - Jain, Rajeev; Shivankar, Bhavana R.; Krishnamurty, Sailaja; Al-Khateeb, Lateefa A.; Sheetal, Sarah; Alharthi, Sarah (Sustainable Chemistry and Pharmacy, 2025)
A novel disposable in-tip cellulose paper (DICP) device, enhanced with clove essential oil (CEO), was developed for the extraction of four anesthetic drugs (lidocaine, prilocaine, ropivacaine, and bupivacaine) from postmortem blood and urine samples. The DICP device, equipped with 1 x 3 cm CEO-impregnated cellulose paper (CP) strips (prepared via a simple dip-coating process), is attached to a 1000 mu L micropipette. The findings from density functional theory (DFT) study reveals that CEO-impregnated cellulose demonstrates stronger and more diverse interactions with anesthetic drugs, as evidenced by more negative adsorption energy (-0.62 eV) and enhanced non-covalent interactions compared to cellulose alone. The procedure involves aspirating and dispensing diluted biological samples through the DICP device for 30 cycles, adsorbing the analytes onto the CEO-impregnated CP strips. The adsorbed analytes are subsequently eluted with 0.5 mL of ethyl acetate through 40 aspirating-dispensing cycles and analyzed by GC-MS. The method achieved limits of quantification as low as 0.01 mu g/mL, with intra-day and inter-day precisions below 10.2 % and 14.6 %, respectively, and accuracy ranging from 90.5 % to 110.7 %. Relative recoveries ranged from 66 % to 87.6 %, while matrix effects remained consistently below 11.9 %. The DICP-GC-MS method demonstrated exceptional sustainability, achieving a whiteness score of 97.2 %, underscoring its alignment with green analytical chemistry principles and operational simplicity. Applicability was demonstrated through the successful analysis of postmortem cardiac blood in a suspected anesthetic drug overdose case, highlighting its potential as a robust, high-throughput, and eco-friendly approach for routine forensic toxicological screening.
Keywords: Anesthetic drugs; Clove essential oil; Disposable in-tip cellulose paper (DICP) device; Green sample preparation; White analytical toxicology (WAT)

Effect of cyclization and alkyl group wrapping in visible-light-active unsymmetrical squaraine dyes for dye-sensitized solar cells - Jadhav, Avinash P.; Singh, Ambarish Kumar; Shivankar, Bhavana R.; Siby, Jesna; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (ACS Applied Energy Materials, 2025)
A series of alkyl group-appended indoline- and carboxylic acid-functionalized indolenine-based visible-light-active unsymmetrical squaraine dyes, SQA7-10, were designed, synthesized, and utilized for the dye-sensitized solar cells device fabrication. The number of alkyl group has been increased systematically on the indoline moiety to control the self-assembly of dyes on TiO2 and to passivate the photoanode that helps in improving the open-circuit voltage (V-OC) by avoiding the charge recombination process. SQA7-10 dyes showed an absorption between lambda(max) 536-540 nm, with molar extinction coefficients of 1.62-2.13 x 10(5) M-1 cm(-1) in CH3CN. Further, ultraviolet-visible (UV-vis) studies on TiO2 indicated the formation of H-aggregated dyes (505-510 nm), which can be controlled by appending the alkyl groups. The energy levels of the highest occupied molecular orbital (HOMO) of these dyes are well aligned with the Nernst potentials of I-/I(3)(-)electrolyte and [Cu(tmby)(2)](+/2+) electrolytes with sufficient overpotentials required for the dye regeneration process. DSSC devices made with these dyes showed systematic enhancements of open-circuit voltage (V-OC) and device efficiency with respect to alkyl group incorporation for SQA7-10 with I-/I-3(-) electrolytes. All of the SQA dyes exhibited the device V-OC of more than 805 mV, where the introduction of alkyl groups systematically enhanced the V-OC in the order of SQA7 (805 mV) < SQA8 (829 mV) < SQA9 (843 mV) < SQA10 (862 mV) without any addition of CDCA. Within the SQA dye series, SQA10 dye has achieved the highest DSSC device efficiency of 7.52% (J(sc) of 11.16 mA/cm(2), V-oc of 862 mV, and ff of 78%) with I-/I-3(-) electrolyte, whereas use of [Cu(tmby)(2)](+/2+) redox shuttle with SQA10 showed enhanced V-oc (1080 mV) and device efficiency (8.35%). The IPCE profile for the device fabricated with SQA dyes showed good response at 480 and 560 nm, which indicates the photocurrent generation from the aggregated structures.
Keywords: aggregation of dyes; charge recombination; Dye-sensitized solar cells; indoline and indolenine donors; visible-light-activeunsymmetrical squaraine dye

Hot injection assisted electronically modulated twin and grain boundary rich sub-2 nm pt3co alloy resistant to phosphate ion for PEMFCs - Singh, Mayank U.; Jadhav, Swapnil D.; Shivankar, Bhavana R.; Pandikassala, Ajmal; Kumar, Yogesh; Krishnamurty, Sailaja; Vinod, C. P.; Kurungot, Sreekumar (Small, 2025)
Modulation of the electronic d-band center, structural defects (line defects), and particle size of Pt3Co alloy electrocatalyst have huge significance in elevating its electrochemical oxygen reduction reaction activity. Deviating from traditional high-temperature strategies, the current work focuses on ripening these benefits by implying a simple economically viable hot-injection-assisted modified polyol process. A conclusive control over decrementing particle size starting from 2.7 to 1.3 nm, an increasing degree of strain (twin boundary), and shifting of the d-band center away from the Fermi level are obtained via varying the temperature to which the solution is injected. The catalyst prepared via the injection at 200 degrees C (Pt3Co(1.3 t,g-b)/fVC-200) has delivered an electrochemical surface area of 84 m(2) g(Pt)(-1) with the onset and half-wave potentials of 0.980 and 0.858 V, respectively, versus RHE and a limiting current of -6.0 mA cm(-2) with stability till 20k cycles. In the high-temperature proton exchange membrane fuel cell Pt3Co(1.3 t,g-b)/fVC-200-based cell has outperformed Pt/C rendering 600 mWcm(-2) under H-2-Air compared to 529 mWcm(-2) of Pt/C with 20% lower Pt loading and double the stability due to enhanced resistance toward phosphoric acid for accelerated voltage cycling. A similar enhancement is seen while employing the catalyst for low-temperature fuel cells.
Keywords: electrocatalyst; grain boundary; hot injection synthesis; modified polyol process; oxygen reduction reaction; proton exchange membrane fuel cell; Pt3Co alloy; twin boundary; valance band X-ray photoelectron spectroscopy

In silico designing of electrocatalysts for hydrogen evolution reaction: a focus on titanium metal-based diboride monolayers - Shivankar, Bhavana R.; Verma, Tushar Singh; Krishnamurty, Sailaja (International Journal of Hydrogen Energy, 2025)
Enhancing the efficiency of Hydrogen Evolution Reaction (HER) using chemically modified electrocatalytic titanium diboride surfaces with transition metal-based Single Atom Catalysts (SACs) is illustrated using Density Functional Theory (DFT) based methods employing solvent effects. With higher surface concentrations of nonmetal boron rather than titanium metal, these highly conductive, extremely hard, chemically, and thermally stable electrocatalysts are more cost-effective and superior to their MBene analogs. A systematic analysis of these transition metal-based SACs from the 3d, 4d, and 5d groups embedded in TiB2 monolayer for its HER activity reveals the reduction in limiting potential. As the most effective SAC for improved HER, Zn@TiB2 SAC has a limiting potential of 0.08 eV in acidic and 0.21 eV in alkaline media. The higher exchange current density of Zn@TiB2 (5.74 x 10-5 A cm-2), which exceeds most previously reported electrocatalysts, indicates exceptional HER performance. This work shows that transition metal boride electrocatalysts are economically viable for HER and pave a path for experimentalists.
Keywords: AIMD; D -band center; DFT; HER; SAC